Cytosolic calcium ions exert a major influence on the firing rate and maintenance of pacemaker activity in guinea-pig sinus node - Capel, Rebecca A.; Terrar, Derek A. (Frontiers in Physiology, 2015)
The sino-atrial node (SAN) provides the electrical stimulus to initiate every heart beat. Cellular processes underlying this activity have been debated extensively, especially with regards to the role of intracellular calcium. We have used whole-cell application of 1,2-bis(o-aminophenoxy)ethane-N,N,N',N'-tetraacetic acid (BAPTA), a rapid calcium chelator, to guinea pig isolated SAN myocytes to assess the effect of rapid reduction of intracellular calcium on SAN cell electrical activity. High-dose (10 mM) BAPTA induced rapid and complete cessation of rhythmic action potential (AP) firing (time to cessation 5.5±1.7 s). Over a range of concentrations, BAPTA induced slowing of action potential firing and disruption of rhythmic activity, which was dose-dependent in its time of onset. Exposure to BAPTA was associated with stereotyped action potential changes similar to those previously reported in the presence of ryanodine, namely depolarisation of the most negative diastolic potential, prolongation of action potentials and a reduction in action potential amplitude. These experiments are consistent with the view that cytosolic calcium is essential to the maintenance of rhythmic pacemaker activity.